The specification of dynamic discrete-time two-state panel data models - Tue Gørgens; Dean Robert Hyslop (Econometrics, 2019)
This paper compares two approaches to analyzing longitudinal discrete-time binary outcomes. Dynamic binary response models focus on state occupancy and typically specify low-order Markovian state dependence. Multi-spell duration models focus on transitions between states and typically allow for state-specific duration dependence. We show that the former implicitly impose strong and testable restrictions on the transition probabilities. In a case study of poverty transitions, we show that these restrictions are severely rejected against the more flexible multi-spell duration models.
Keywords: C33; C35; C41; C51; 330; panel data; transition data; binary response; duration analysis; event history analysis; dynamic models; censored data; initial conditions; random effects